CD30-positive cutaneous lymphoma: report of four cases with an emphasis on clinicopathological correlations - Thiago Jeunon de Sousa Vargas; Samira Barroso Jorge; Yung Bruno de Mello Gonzaga (Sociedade Brasileira de Dermatologia, 2017)
Abstract: The classification of cutaneous lymphomas is multidisciplinary and requires the correlation between clinical, histopathological, immunohistochemical, and molecular diagnostic elements. In this article, we present four different cases of CD30-positive T-cell lymphoma with cutaneous manifestations. We compare cases with definitive diagnosis of papulosis lymphomatoid type C, primary cutaneous anaplastic large T-cell lymphoma, systemic anaplastic large T-cell lymphoma with secondary skin involvement, and mycosis fungoides with large cell transformation, highlighting the importance of clinicopathological correlation to classify these cases.